The Role of Interpersonal Skills of Village-Owned Enterprise (BUM Desa) Managers in East Sumba Regency Facing the Challenges of Changing Economic Structures - Fransiskus Xaverius Candra Gunawan; Husnah Rahman; Andi Tenri Awaru (Research and Development Agency Ministry of Home Affairs, 2024)
In the current era of information technology and digitalization, the transformation of structural changes in the economy seems to be running so fast that it exceeds the readiness factor of the community itself. As a result, the impact of development only results in achieving macroeconomic targets. At the same time, micro-scale economic solutions often experience setbacks, as experienced by most rural communities in East Sumba Regency, characterized as farmers and Sumba ikat weavers with relatively low family income and education levels. Therefore, it is important to strengthen the institutional role of BUM Desa, especially the human resources of administrators, as the driving force of economic development in rural areas. This study aims to analyze how the relationship between interpersonal skills affects organizational performance by applying good corporate governance principles. The research method uses quantitative descriptive analysis techniques sourced from secondary and primary data with a Likert scale approach. The results of the analysis of 144 respondents in 30 active BUM Desa based on SEM analysis showed that interpersonal skills factors have a positive and significant effect on implementing good corporate governance and performance. In addition, the relationship between implementing good corporate governance and performance has a positive and significant effect. This research recommends the need for government efforts to improve the work motivation of administrators at the beginning of their careers, such as 1. providing a reward system that is commensurate with employment regulations and 2. increasing cooperation and partnerships in the development of the micro, small, and medium business sector. On the other hand, the implications of this study state that BUM Desa institutions with good human capital are the main actors in developing smart villages as an answer to the challenges and threats of structural economic change.